2020
DOI: 10.17784/mtprehabjournal.2020.18.810
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and chronic pain in community dwelling older adults: preliminary results

Abstract: Background: The natural process of human aging causes biopsychosocial alterations, which can trigger chronic pain and poor sleep quality in older adults. Considering the high prevalence and possible association between these two clinical conditions, special attention from public health policies is necessary to provide quality aging. Objective: To verify if there is an association between chronic pain and sleep quality among older adults in the community. Methods: A quantitative, cross-sectional study on the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…These data are supported by a previous study that demonstrated the influence of an alpha band training (NFT) on HRV [ 59 ]. Recently, a case study was carried out on a patient with stroke and it was found that NFT had a positive effect on increasing HRV [ 60 ]. Although this is only one case and belongs to a very different from that observed in this study, the results are in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These data are supported by a previous study that demonstrated the influence of an alpha band training (NFT) on HRV [ 59 ]. Recently, a case study was carried out on a patient with stroke and it was found that NFT had a positive effect on increasing HRV [ 60 ]. Although this is only one case and belongs to a very different from that observed in this study, the results are in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%